TOLERANSI BERAGAMA ERA DIGITAL : (Studi Atas Podcast Habib Husein Ja'far Al-Haddar) - Fathul Bari; Isnaini Fauzia Jamila (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
The study of religious tolerance should be a concern for countries that have a multicultural society like Indonesia, in order to maintain harmony and peace in diversity. With the rapidly developing digital era, it is hoped that the study of religious tolerance can be distributed to all levels of society in Indonesia. This research method uses a qualitative approach with social media analysis. Data is obtained by the flow of capture, understand, dan present. The results of the study, that the sophistication of digital social media can be used as a publication of religious tolerance in a multicultural society. Keywords: Religious Tolerance, Digital Era